CONTEXTUALIZATION OF THE CONCEPT OF AT-TAMATSIL IN THE STORIES OF THE QUR'AN: Perspective of Maqashidi Interpretation - Andersa, Aan; Yuningsih, Hartati (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
This study examines the contextualization of the concept of at-Tamatsil in the stories of the Qur'an, noted in the Qur'an its application contains contradictory where applied as an object of theology in the story of the people of prophet Ibrahim and on the other hand applied without involving theological elements applied by prophet Solomon. The purpose of this research is to see the maqashid of the word at-Tamatsil in the stories of the Qur'an by using the maqashidi interpretation method. In this case, the author uses Abdul Mustaqim's Maqashidi interpretation method in analyzing maqashid which is framed in seven basics (Hifdz al-Din, al-Nafs, al-`Aql, al-Nasl, al-Mal, ad-Daulah and al-Bi'ah) to reveal the maqashid of at-Tamatsil. This research uses a qualitative approach with the method of literature (library research). The results showed that in Hifdz al-Din as a motivator in devotion to Allah Swt., aspects of Hifdz al-Nafs and Hifdz al-`Aql as a means towards a person who is Ulul al-Bab, and aspects of Hifdz al-Nasl and Hifdz al-Mal as career prospects. This research contributes to the search for maqashid regarding at-Tamatsil and can provide insight for Qur'anic studies and fiqh research.